Masjid dan Perubahan Masyarakat Pascaindustri di Indonesia: Amalan NU dalam Bingkai Muhammadiyah - Saifullah, Muhammad (Jurnal Sosiologi Agama, 2018)
Muhammadiyah was frequently being similarized with who denied tradition and NU was not. Though one tries to coerce, it will be merely culture movement without tradition. This article desires to look further the soft contestation which is occurred between Muhammadiyah and NU’s movement within Masjid Jendral Sudirman (MJS). MJS is one of mosque in Yogyakarta whose Muhammadiyah affiliation, yet almost all activities therein use NU’s peculiarities. Boards (takmir) enliven the mosque were coming from NU since 2008 and so that it is decently plausible. I’m interesting to investigate what actually happened beyond the board’s movement in instilling NU’s particularities upon Muhammadiyah’s mosque: is it insurgency, coup d’etat, or a new mode of hybrid, and why it can be occurred. The article thus argues that the pattern of NU’s board movement in MJS is merely mass movement which emerges unconsciously as an effect of unawareness shift, borrowing Selo Soemardjan’s phrase. The shift which is entangled society change in postindustrial, internet milieu. Keywords: Masjid Jendral Sudirman (MJS), Muhammadiyah and NU, Mass movement, unconscious shift, postindustrial society.